A novel electrochemical method based on screen-printed electrodes and magnetic beads for detection of trinucleotide repeat sequence d(CAG)n. (17th May 2018) - Liu, Yalan; Li, Jiao; Chang, Gang; Zhu, Ruizhi; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Abstract : The combination of SPCE and magnetic beads simplifies the experimental procedure, which is useful for early diagnosis of trinucleotide repeat diseases. Abstract : Electrochemical sensors have been highly developed and play an important role in the early diagnosis of different diseases. In this work, a simple and rapid electrochemical method was developed for the quantitative detection of a trinucleotide repeat (TNR) sequence d(CAG) n based on magnetic beads and screen-printed carbon electrodes. Their combination greatly simplified the operation process. The intensity of the electrochemical signal was linearly correlated against the concentration of the TNR sequence d(CAG) n in the range from 100 pM to 1 μM, with a limit of detection as low as 24 pM. Furthermore, the number of repeats of the TNR sequence d(CAG) n could be detected and also showed a good linear relationship. The proposed method provides a promising rapid and simple method for the detection of a CAG TNR sequence for point-of-care testing in clinical applications.